Developing a customised approach for strengthening tuberculosis laboratory quality management systems toward accreditation - Heidi Albert; Andre Trollip; Donatelle Erni; Kekeletso Kao (AOSIS, 2017)
Background: Quality-assured tuberculosis laboratory services are critical to achieve global and national goals for tuberculosis prevention and care. Implementation of a quality management system (QMS) in laboratories leads to improved quality of diagnostic tests and better patient care. The Strengthening Laboratory Management Toward Accreditation (SLMTA) programme has led to measurable improvements in the QMS of clinical laboratories. However, progress in tuberculosis laboratories has been slower, which may be attributed to the need for a structured tuberculosis-specific approach to implementing QMS. We describe the development and early implementation of the Strengthening Tuberculosis Laboratory Management Toward Accreditation (TB SLMTA) programme. Development: The TB SLMTA curriculum was developed by customizing the SLMTA curriculum to include specific tools, job aids and supplementary materials specific to the tuberculosis laboratory. The TB SLMTA Harmonized Checklist was developed from the World Health Organisation Regional Office for Africa Stepwise Laboratory Quality Improvement Process Towards Accreditation checklist, and incorporated tuberculosis-specific requirements from the Global Laboratory Initiative Stepwise Process Towards Tuberculosis Laboratory Accreditation online tool. Implementation: Four regional training-of-trainers workshops have been conducted since 2013. The TB SLMTA programme has been rolled out in 37 tuberculosis laboratories in 10 countries using the Workshop approach in 32 laboratories in five countries and the Facility based approach in five tuberculosis laboratories in five countries. Conclusion: Lessons learnt from early implementation of TB SLMTA suggest that a structured training and mentoring programme can build a foundation towards further quality improvement in tuberculosis laboratories. Structured mentoring, and institutionalisation of QMS into country programmes, is needed to support tuberculosis laboratories to achieve accreditation.